Hubungan Kualitas Asuhan Keperawatan dengan Kepuasan Pasien - Barus, Yosafat (Lembaga Teewan Journal Solutions, 2026)
The quality of nursing care is an important indicator in assessing the quality of health services because it is directly related to patient experience and satisfaction during treatment. Quality nursing care includes aspects of communication, responsiveness, empathy, service assurance, and the ability to meet patient needs. This study aims to analyze the relationship between the quality of nursing care and patient satisfaction in the inpatient ward of Bina Kasih Hospital, Medan in 2026. Method: The study used a correlational analytical design with a cross-sectional approach. The sample consisted of 36 inpatients selected using accidental sampling techniques. Data were collected using a nursing care quality questionnaire based on SERVQUAL dimensions and a patient satisfaction questionnaire. Data analysis was carried out univariately and bivariately using the Chi-Square test with a significance level of 95% (α = 0.05). Results: A total of 20 respondents rated the quality of nursing care as good, with 18 respondents (90.0%) feeling satisfied. In the group that rated the quality of nursing care as poor, the majority of respondents (62.5%) stated that they were dissatisfied. The results of the Chi-Square test showed a significant relationship between the quality of nursing care and patient satisfaction (p=0.002). The Odds Ratio value of 18.00 (95%CI=2.72–119.02) indicates that patients who receive good quality nursing care have an 18 times greater chance of feeling satisfied than patients who receive poor nursing care. Conclusion: The quality of nursing care is significantly related to patient satisfaction, so improving the quality of nursing services needs to be a priority in efforts to improve the quality of hospital services.